Samsung Galaxy Tab S2 Nook for dummies - Sandler, Corey, 1950- (--For dummies., 2016)
Your Tab S2 NOOK hides a lot of versatility behind its modest screen. Discover all the features of a computer tablet that are built in to your NOOK, explore all the built-in apps, and learn to maximize use of the calendar, notes, contacts and email contacts.